Efektifitas Edukasi COVID-19 Secara Daring Pada Kelompok Dukungan Sebaya Top Support Yayasan Pelita Ilmu - ruri mutia ichwan; Hadi Pratomo; Putri Diyah Patni; Dame Artha Ria; Reza Dara Pertiwi; Andi M Yusuf Ridwan; Farandi Agesti Ramadhan (Jurnal Kesehatan Komunitas, 2021)
Abstract Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that can cause mild disorders of the respiratory system, severe lung infections, and death. The large number of confirmed cases is positive, giving special attention to groups that are vulnerable to infection such as groups with immunodeficiency, one of which is the group of people with HIV. This study aims to assess the effectiveness of presenting online COVID-19 education to increase knowledge, attitudes and practices to prevent COVID-19 in the Peer Support Group (KDS) Top Support Pelita Ilmu Foundation (YPI) located in Jakarta. This study used a qualitative method. Target of interventions are mentors and peer educators. Data were collected through semi-structured interviews, self-administered questionnaire and report. The data analysis technique was carried out with three main activities, namely: data reduction, data presentation, and drawing conclusions. The validity of the data was carried out by means of credibility through the triangulation of sources and methods. The results showed that providing COVID-19 education online by involving mentoring and empowering peer educators was effective in increasing knowledge about the COVID-19 prevention protocol. Providing online educational assistance through a peer educator approach is useful as a chain message to oneself, family, community and peers. People who are educated are becoming more diligent in implementing 3M and healthy lifestyles, but to know this behavior change consistently, further research is needed.